Novel TiC composite ceramic and preparation method thereof

By introducing C vacancy in TiC, using the direct introduction vacancy method and in-situ synthesis vacancy method, the problem of high sintering temperature and low toughness of TiC composite ceramics is solved, and the effect of preparing dense and high toughness of TiC composite ceramics at lower temperatures is achieved.

CN119710419APending Publication Date: 2025-03-28YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036697.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

TiC composite ceramics have problems with high sintering temperature and low toughness, which are difficult to meet the requirements of scientific and technological development for materials.

Method used

The introduction of C vacancy in TiC by direct introduction vacancy method and in-situ synthetic vacancy method reduces the sintering temperature and improves toughness. The specific method includes adding TiC0.4 or metals Ti, V, Zr to TiC, and preparing dense TiC composite ceramics through mechanical alloying and discharge plasma sintering processes.

Benefits of technology

The high density TiC composite ceramics were successfully prepared at lower temperatures, which improved their fracture toughness and improved interface strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710419A_ABST
    Figure CN119710419A_ABST
Patent Text Reader

Abstract

The invention provides novel TiC composite ceramic and a preparation method thereof. The novel TiC composite ceramic is prepared by taking TiC, Ti, V and Zr as raw materials. The preparation method comprises the following steps: preparing non-stoichiometric ratio TiC0.4 by adopting a mechanical alloying method, and carrying out mechanical alloying on the non-stoichiometric ratio TiC0.4 and TiC according to the proportion of TiC-xTiC0.4 (x is equal to 10wt.%, 14wt.%, 20wt.%) to prepare powder before sintering; tiC, Ti, V and Zr are subjected to mechanical alloying according to the proportion of TiC-xTi (x = 3.63 wt%, 5.63 wt%, 7.63 wt% and 10.63 wt%) and the molar ratio of 9TiC-0.5 Ti-0.5 Zr to 9TiC-0.5 Ti-0.5 V to prepare powder before sintering; the mixed powder is put into a mold to be pre-pressed; and sintering by adopting a spark plasma sintering process to prepare the novel TiC composite ceramic material. The mixed powder is put into a mold to be pre-pressed; and sintering the pre-pressed sample by adopting a spark plasma sintering process to prepare the novel TiC composite ceramic material. According to the research, vacancies are introduced into TiC by adding TiC0.4 to directly introduce vacancies and adding Ti, Zr and V to synthesize vacancies in situ, so that the sintering temperature of the TiC composite ceramic is effectively reduced, and the toughness of the TiC composite ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite ceramic materials, and in particular to a novel TiC composite ceramic and a preparation method thereof. Background Art

[0002] TiC has a high melting point (3060 ℃), high hardness (30 GPa), good chemical and thermal stability, excellent wear resistance and corrosion resistance. As an important structural ceramic material, TiC composite ceramics have been widely used in high-tech fields such as machinery, aviation, and microelectronics.

[0003] A large number of literature reports have been published on the strengthening and toughening of TiC composite ceramics by adding a second phase. Cheng Lixia et al. prepared TiC-SiC composite ceramics by spark plasma sintering (SPS) process. The results showed that the addition of SiC improved the fracture toughness of the TiC matrix and refined the TiC grains. The hardness of the TiC-SiC composite ceramics prepared with SiC addition of 0 vol.% and 14.6 vol.% were 28.9 GPa and 20.3 GPa, respectively, and the toughness was 4.3±0.4 MPa·m 1 / 2 and 5.2±0.6 MPa·m 1 / 2 [Cheng Lixia, Xie Zhipeng, Xue Weijiang, et al. Preparation and characterization of TiC-SiC composite ceramics by spark plasma sintering [J]. Rare Metal Materials and Engineering, 2013, 42(Supplement 1):293-296.]. Liu Xiaohong et al. showed that SiC and TiC have excellent compatibility, and the addition of SiC has a significant effect on improving the fracture toughness of composite ceramics. The fracture strength of the 30wt.% SiC sample is 116% higher than that of the pure TiC material [Liu Xiaohong, Wang Yanfeng, Cao Yongdi, et al. Research on the preparation of TiC / SiC composite reinforced materials by spark plasma sintering [J]. Steel Vanadium Titanium, 2021, 42(6):153-157.]. Xu Guangping et al. added 0~90wt.% nano-TiC to TiC micropowder with a particle size of about 3 μm, and prepared TiC high-temperature composite ceramics by SPS sintering process at 1600 ℃ for 5 min. The results show that when the addition amount of nano-TiC is 10wt.%, the hardness of TiC composite ceramics is 24GPa and the fracture toughness is 4.5 MPa·m 1 / 2[Xu Guangping, Song Yihua, He Jiangrong, et al. Effect of nano-TiC addition on sintering and mechanical properties of TiC high temperature ceramics [J]. Refractories, 2013, 47(6):410-413.] Song Guiming et al. prepared carbon fiber (20 vol.% carbon fiber) reinforced TiC composite ceramics by hot pressing sintering process. The results showed that the short carbon fiber that is easy to agglomerate is uniformly dispersed in the TiC matrix by ball milling wet mixing process. The optimal hot pressing sintering temperature of Cf / TiC composite ceramics is 2100 ℃, the room temperature flexural strength of the composite ceramics is 593 MPa, and the fracture toughness is 6.87 MPa·m 1 / 2 , and the high temperature flexural strength at 1400 ℃ is 439 MPa [Song Guiming, Wu Ying. Preparation and high temperature strength of carbon fiber reinforced TiC composites [J]. Materials Engineering, 2001, 9:3-17.].

[0004] In summary, the current TiC composite ceramics have shortcomings such as high sintering temperature and low toughness. In order to make TiC composite ceramics meet the requirements of scientific and technological development for materials in terms of production, preparation and performance, it is urgently necessary to develop new methods to improve the problems of high sintering temperature and low toughness. Summary of the invention

[0005] The present invention introduces C vacancies into TiC by using two methods: direct vacancy introduction method and in-situ vacancy synthesis method, so as to reduce the sintering temperature of TiC composite ceramics and improve its toughness. 0.4 Add to TiC; the in-situ synthesis vacancy method is to add metal Ti, V, Zr to TiC to form C vacancies through in-situ reaction. 0.4 The mixed powder before sintering is prepared by mechanical alloying method, and the sintered body is prepared by spark plasma sintering process. The TiC composite ceramic with high density is successfully prepared at a lower temperature, and its fracture toughness is improved.

[0006] By adding TiC 0.4 A new type of TiC composite ceramic material was prepared by directly introducing vacancies and adding metal Ti, V, and Zr to synthesize vacancies in situ. Its phase composition is TiCx phase with different x values. The TiC cemented carbide is designed to have the following composition according to mass percentage: TiC-xTiC 0.4 (x=10, 14, 20 wt.%), TiC-xTi(x=3.63, 5.63, 7.63, 10.63 wt.%); the designed composition according to the molar ratio is: 9TiC-0.5Ti-0.5Zr(V).

[0007] The present invention also discloses a method for preparing the novel TiC composite ceramic, which is characterized by comprising the following steps: S1、TiC 0.4 Preparation: TiC and Ti powder were mixed in a ball mill in a glove box filled with argon gas at a ratio of Ti:C = 1:0.4 (molar ratio), and the ball-to-material mass ratio was 20:1. The rotation speed was 450 r / min, and the ball milling time was 60 h. The mill was stopped for 30 min every 1 h to dissipate heat. After 30 h of ball milling, the mill was stopped to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank, and then the mixture was mixed and continued to ball mill to obtain TiC 0.4 Powder.

[0008] S2. Preparation of mixed powder: In a glove box filled with argon, TiC powder was mixed with TiC prepared in S1. 0.4 Powder and metal Ti, V, Zr powder according to TiC-xTiC 0.4 (x=10-20wt.%), TiC-xTi(x=3.63-10.63 wt.%) and TiC-0.5Ti-0.5Zr(V) with a molar ratio of 9 were mixed and loaded into the ball mill, with a ball-to-material mass ratio of 20:1. The rotation speed was 450 r / min, the ball milling time was 2-60 h, and the machine was stopped for 30 min for heat dissipation every 1 h. When the ball milling time was greater than 10 h, 0.4 ml of alcohol was added as a dispersant for every 10 g of powdered raw material. When the ball milling time was greater than 20 h, the material should be emptied once in the middle of the ball milling.

[0009] S3, sintering preparation: the mixed material of step S2 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is carried out, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1500-1700 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0010] Furthermore, the purity of the TiC, Ti, V and Zr powders is greater than 99.5%, and the particle sizes are all 1 to 3 μm.

[0011] Furthermore, in the ball milling processes of steps S1 and S2, three large, medium and small sizes of WC cemented carbide balls with diameters of 8 mm, 5 mm and 2 mm were used, wherein the mass ratio of the large, medium and small WC cemented carbide balls was 6:3:1.

[0012] Furthermore, the specific sintering process in step S3 is: first, slowly apply pressure to the sample to 40 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600 °C in 5 min, and keep at 600 °C for 10 min; then heat from 600 °C to the final sintering temperature at a heating rate of 100 °C / min, and keep for 10 min; cool with the furnace to obtain a blank; perform surface grinding and deburring on the blank to obtain a new TiC composite ceramic.

[0013] Compared with the prior art, the present invention has the following advantages: The present invention adds TiC 0.4 Or metal Ti, Zr, and V introduce C vacancies into TiC, which makes the atomic diffusion during the sintering process more intense, promotes the bonding between TiC grains, and improves the interface strength. The final TiC composite ceramic contains TiC phases with different Ti / C and has higher toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 XRD diagrams of the novel TiC composite ceramics provided by the present invention: (a) XRD diagram of the TiC composite ceramic in Example 1; (b) XRD diagram of the TiC composite ceramic in Example 5; (c) XRD diagram of the TiC composite ceramic in Example 7.

[0015] Figure 2 SEM images of TiC composite ceramics: (a) SEM image of the surface and cracks of the TiC composite ceramic in Example 1; (b) SEM image of the fracture of the TiC cemented carbide in Example 1; (c) SEM image of the surface of the TiC composite ceramic in Example 5; (d) SEM image of the fracture of the TiC composite ceramic in Example 5; (d) SEM image of the surface of the TiC composite ceramic in Example 7.

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0018] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0019] Unless otherwise specifically stated, the relative arrangement of the parts and steps described in these embodiments, numerical expressions and numerical values ​​do not limit the scope of the present invention. At the same time, it should be clear that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be regarded as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.

[0020] The present invention provides a novel TiC composite ceramic material, wherein the TiC composite ceramic material is TiC-xTiC 0.4 (x=10-20wt.%), TiC-xTi (x=3.63-10.63wt.%) and TiC hard alloy with a molar ratio of 9TiC-0.5Ti-0.5Zr(V). The purity of the TiC, Ti, V and Zr powders is greater than 99.5%, and the particle size is 1-3 μm.

[0021] The ball mill model described in the present invention is QM-3SP4 (China).

[0022] The spark plasma sintering apparatus described in the present invention is of model LABOXTM-110 (Japan).

[0023] Graphite molds are products currently sold on the market.

[0024] The detection equipment described in the present invention are all instruments used for conventional detection means in university laboratories, such as X-ray diffractometer, hardness tester, scanning electron microscope, etc. Example 1

[0025] S1. In a glove box filled with argon, the raw materials TiC and Ti powder were weighed according to Ti:C=1:0.4 (molar ratio) and loaded into a WC carbide ball mill. Each can was loaded with 10 g of material, and the ball-to-material mass ratio was 20:1. The speed was 450 r / min, the ball milling time was 60 h, and the machine was stopped for 30 min for heat dissipation after every 1 h of rotation. After 30 h of ball milling, the machine was stopped to scrape off the raw materials stuck to the grinding balls and the inner wall of the can, and then the ball milling was continued to obtain TiC. 0.4 Powder.

[0026] S2. In a glove box filled with argon, TiC powder was mixed with metal Ti and prepared TiC 0.4Powder according to TiC-14wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill, with 10 g of material in a single mill and a ball-to-material mass ratio of 20:1. The speed was 450 r / min, the milling time was 2 h, and the mill was stopped for 30 min every 1 h to allow for heat dissipation.

[0027] S3, loading the mixed material of step S2 into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1600 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0028] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 98.55%, the hardness was 22.5 GPa, and the toughness was 5.2 MPa·m 1 / 2 . Example 2

[0029] S1. In a glove box filled with argon, the raw materials TiC and Ti powder were weighed according to Ti:C=1:0.4 (molar ratio) and loaded into a WC carbide ball mill. A single can was loaded with 10 g of material, including 4.55 g of TiC powder and 5.45 g of Ti powder, and the ball-to-material mass ratio was 20:1. The speed was 450 r / min, the ball milling time was 60 h, and the machine was stopped for 30 min for each hour of rotation to dissipate heat. After 30 hours of ball milling, the machine was stopped to scrape off the raw materials stuck to the grinding balls and the inner wall of the can, and then the ball milling was continued to obtain TiC. 0.4 Powder.

[0030] S2. In a glove box filled with argon, TiC powder was mixed with metal Ti powder and prepared TiC 0.4 Powder according to TiC-14wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill with a ball-to-material mass ratio of 20:1. The rotation speed was 450 r / min, the ball milling time was 10 h, and the mill was stopped for 30 min every 1 h to dissipate heat.

[0031] S3, the mixed material of step S2 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1500 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0032] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 99.27%, the hardness was 18 GPa, and the toughness was 5.74 MPa·m 1 / 2 . Example 3

[0033] S1. In a glove box filled with argon, the raw materials TiC and Ti powder were weighed according to Ti:C=1:0.4 (molar ratio) and loaded into a WC carbide ball mill. Each can was loaded with 10 g of material, and the ball-to-material mass ratio was 20:1. The speed was 450 r / min, the ball milling time was 60 h, and the machine was stopped for 30 min for heat dissipation after every 1 h of rotation. After 30 h of ball milling, the machine was stopped to scrape off the raw materials stuck to the grinding balls and the inner wall of the can, and then the ball milling was continued to obtain TiC. 0.4 Powder.

[0034] S2. In a glove box filled with argon, TiC powder was mixed with metal Ti powder and prepared TiC 0.4 Powder according to TiC-14wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill, with 10 g of material in a single mill and a ball-to-material mass ratio of 20:1. The speed was 450 r / min, the milling time was 2 h, and the mill was stopped for 30 min every 1 h to allow for heat dissipation.

[0035] S3, the mixed material of step S2 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1700 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0036] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 98.8%, the hardness was 19.6 GPa, and the toughness was 5.13 MPa·m 1 / 2 . Example 4

[0037] S1. In a glove box filled with argon, the raw materials TiC and Ti powder were weighed according to Ti:C=1:0.4 (molar ratio) and loaded into a WC carbide ball mill. Each can was loaded with 10 g of material, and the ball-to-material mass ratio was 20:1. The speed was 450 r / min, the ball milling time was 60 h, and the machine was stopped for 30 min for heat dissipation after every 1 h of rotation. After 30 h of ball milling, the machine was stopped to scrape off the raw materials stuck to the grinding balls and the inner wall of the can, and then the ball milling was continued to obtain TiC. 0.4 Powder.

[0038] S2. In a glove box filled with argon, TiC powder was mixed with metal Ti powder and prepared TiC0.4 Powder according to TiC-10wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill, with 10 g of material in a single mill and a ball-to-material mass ratio of 20:1. The speed was 450 r / min, the milling time was 2 h, and the mill was stopped for 30 min every 1 h to allow for heat dissipation.

[0039] S3, loading the mixed material of step S2 into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1600 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0040] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 98.7%, the hardness was 20.98 GPa, and the toughness was 5 MPa·m 1 / 2 . Example 5

[0041] S1. In a glove box filled with argon, TiC powder was mixed with metal Ti powder and prepared TiC 0.4 Powder according to TiC-10wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill, with 10 g of material in a single mill and a ball-to-material mass ratio of 20:1. The speed was 450 r / min, the milling time was 2 h, and the mill was stopped for 30 min every 1 h to allow for heat dissipation.

[0042] S2. In a glove box filled with argon, the raw material TiC and metal Ti were mixed in a ratio of TiC-7.63wt.%Ti and loaded into a WC carbide ball mill, with 10 g of material in each mill and a ball-to-material mass ratio of 20:1. The rotation speed was 450 r / min, the ball milling time was 20 h, and the mill was stopped for 30 min every 1 h for heat dissipation.

[0043] S3, loading the mixed material of step S1 into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1600 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0044] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 99.2%, the hardness was 23.5 GPa, and the toughness was 4.9 MPa·m 1 / 2 . Example 6

[0045] S1. In a glove box filled with argon, TiC powder was mixed with metal Ti powder and prepared TiC 0.4 Powder according to TiC-10wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill, with 10 g of material in a single mill and a ball-to-material mass ratio of 20:1. The speed was 450 r / min, the milling time was 2 h, and the mill was stopped for 30 min every 1 h to allow for heat dissipation.

[0046] S2. In a glove box filled with argon, TiC powder and metallic Ti powder were mixed in a ratio of TiC-7.63wt.%Ti and loaded into a WC carbide ball mill. Each jar was loaded with 10 g of material, and the ball-to-material mass ratio was 20:1. The rotation speed was 450 r / min, and the ball milling time was 10 h. The mill was stopped for 30 min every 1 h to dissipate heat.

[0047] S3, loading the mixed material of step S1 into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1600 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0048] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 98.5%, the hardness was 19.78 GPa, and the toughness was 4.2 MPa·m 1 / 2 . Example 7

[0049] S1. In a glove box filled with argon, TiC powder was mixed with metal Ti powder and prepared TiC 0.4 Powder according to TiC-10wt.%TiC 0.4 The mixture was loaded into a WC carbide ball mill, with 10 g of material in a single mill and a ball-to-material mass ratio of 20:1. The speed was 450 r / min, the milling time was 2 h, and the mill was stopped for 30 min every 1 h to allow for heat dissipation.

[0050] S2. In a glove box filled with argon, TiC powder, metal Ti powder and Zr powder were mixed in a molar ratio of 9TiC-0.5Ti-0.5Zr and loaded into a WC carbide ball mill. Each can was loaded with 10 g of material, and the ball-to-material mass ratio was 20:1. The rotation speed was 450 r / min, the ball milling time was 20 h, and the mill was stopped for 30 min every 1 h for heat dissipation.

[0051] S3, loading the mixed material of step S1 into a graphite mold for pre-compression, the pre-compression pressure is 30 MPa, and the pre-compression is 60 s; then SPS sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40 MPa, the sintering temperature is 1600 ℃, the heating rate is 100 ℃ / min, and the holding time is 10 min; then the temperature is reduced and the pressure is released to obtain a new TiC composite ceramic.

[0052] The sintered TiC composite ceramic sample was ground and polished for microstructure and performance testing. The density was 98.4%, the hardness was 23.7 GPa, and the toughness was 5.4 MPa·m 1 / 2 .

[0053] Taking Example 1, Example 5 and Example 7 as examples, TiC-14wt.%TiC 0.4 The XRD patterns of the sintered bodies of TiC-7.63wt.%Ti and 9TiC-0.5Ti-0.5Zr only contain TiCx peaks, indicating that the added metals are all dissolved in TiC. Due to the low addition amount, the peak of the generated solid solution cannot be detected or the solid solution peak overlaps with the TiC peak. From the surface morphology, it can be seen that the sintered body has a high degree of densification, no obvious pores are seen, and there are crack deflection and bridging. TiC 0.4 The addition of plays a role in strengthening the bonding strength between grains, and the fracture morphology of the sintered body shows that its fracture mode is transgranular fracture.

[0054] It can be seen from Examples 1-7 that the mechanical alloying time, sintering temperature and TiC 0.4 The addition of V and Zr has a significant effect on the properties of TiC composite ceramics. The addition of metal V and Zr further improves the properties of TiC. 0.4 The hardness of the composite ceramic is significantly reduced and the toughness is improved. It can be seen from Examples 1 and 3 that as the sintering temperature increases from 1600°C to 1700°C, the TiC-14wt.%TiC 0.4 The hardness of the composite ceramic decreases significantly, and the toughness also decreases slightly. It can be seen from Examples 5 and 7 that the addition of metal Zr significantly improves the fracture toughness of the TiC-Ti composite ceramic while maintaining high hardness.

[0055] In summary, the present invention adds TiC 0.4 Or metal Ti, Zr, and V introduce C vacancies into TiC, which makes the atomic diffusion during the sintering process more intense, promotes the bonding between TiC grains, and improves the interface strength. The final TiC composite ceramic contains TiC phases with different Ti / C and has higher toughness.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A new type of TiC composite ceramic, characterized in that: By adding TiC 0.4 A new type of TiC composite ceramic material was prepared by directly introducing vacancies and adding metal Ti, V, and Zr to synthesize vacancies in situ. Its phase composition is TiCx phase with different x values. The TiC cemented carbide is designed to have the following composition according to mass percentage: TiC-xTiC 0.4 (x=10, 14, 20 wt.%), TiC-xTi(x=3.63, 5.63, 7.63, 10.63 wt.%); the designed composition according to the molar ratio is: 9TiC-0.5Ti-0.5Zr(V).

2. A method for preparing the novel TiC composite ceramic according to claim 1, characterized in that: The following steps are included: S1、TiC 0.4 Preparation: TiC 0.4 The preparation of TiC and Ti powders was carried out using a planetary ball mill, WC carbide ball mill and WC carbide grinding balls. TiC and Ti powders were weighed and loaded into the ball mill according to a certain ratio, with a ball-to-material ratio of 20:

1. The air was evacuated in the glove box, filled with argon and 0.2-0.5 ml of alcohol was added; the ball mill speed was 450 r / min, the total ball milling time was 60 h, and the material was dumped after 30 h; S2. Preparation of mixed powder: The mixed powder is prepared using a planetary ball mill, WC carbide ball mill and WC carbide grinding balls. The materials are weighed and loaded into the ball mill according to a certain ratio, with a ball-to-material ratio of 20:

1. The air is evacuated in the glove box, filled with argon and 0.2-0.5 ml of alcohol is added. The ball mill speed is 450 r / min, and the ball milling time is 2-60 h; S3, sintered body preparation: the mixed powder prepared by step S2 is loaded into a graphite mold with a diameter of 10 mm and pre-pressed at a pre-pressing pressure of 30 MPa for 60 s; then spark plasma sintering is performed with a vacuum degree of 40 Pa, a sintering pressure of 40 MPa, a sintering temperature of 1500-1700 °C, a heating rate of 100 °C / min, and a holding time of 10 min; then the temperature is reduced and the pressure is released to obtain a TiC composite ceramic sintered body.

3. The method for preparing the novel TiC composite ceramic according to claim 2, characterized in that: All raw material powders have a particle size of 1~3 µm and a purity of >99.5%.

4. The method for preparing the novel TiC composite ceramic according to claim 2, characterized in that: The ball milling process of steps S1 and S2 uses three types of large, medium and small WC cemented carbide balls with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small WC cemented carbide balls is 6:3:

2.

5. The method for preparing the novel TiC composite ceramic according to claim 2, characterized in that: The mixed powder in step S2 is prepared by a mechanical alloying method, and the mechanical alloying process parameters are as follows: ball-to-material ratio is 20:1, ball milling speed is 450 r / min, and ball milling time is 2-60 h.

6. The method for preparing the novel TiC composite ceramic according to claim 2, characterized in that: The specific sintering process in step S3 is as follows: first, slowly apply pressure to the sample to 40-50 MPa; then, evacuate to 40 Pa; then, heat from room temperature to 600 °C in 5 minutes, and keep at 600 °C for 10 minutes; then, increase the temperature from 600 °C to 1500-1700 °C at a heating rate of 30-100 °C / min, and keep for 10 minutes; cool with the furnace to obtain a blank; perform surface grinding and polishing on the prepared blank to obtain a new TiC composite ceramic material.